# Simple Algebra Q: x * 3 + (1 - x) * 11 = 7

#### Leo516

##### New member
Can someone help me with this problem?

x * 3 + (1 - x) * 11 = 7

if I get rid of the parenthesis I’m left with:
x * 3 + 1 - x * 11 = 7

then I’m not sure what to do. If I combine the “x”s they will cancel out, so I thought maybe I should start with the multiplication and try to work through
3x + 1 - 11x = 7
-8x = 6
x= -.75
But I know it is wrong because x is obviously .5

Can someone tell me where I went wrong?

#### Mrspi

##### Senior Member
Re: Simple Algebra Question

Leo516 said:
Can someone help me with this problem?

x * 3 + (1-x) * 11 = 7

if I get rid of the parenthesis I’m left with:
x * 3 + 1 - x * 11 = 7

then I’m not sure what to do. If I combine the “x”s they will cancel out, so I thought maybe I should start with the multiplication and try to work through
3x + 1 - 11x = 7
-8x = 6
x= -.75
But I know it is wrong because x is obviously .5

Can someone tell me where I went wrong?
Doing the multliplications first is an excellent idea. However, you forgot that both terms inside the parentheses must be multiplied by 11:

3*x + 11*1 - 11*x = 7
3x + 11 - 11x = 7
Combine like terms:
-8x + 11 = 7

Subtract 11 from both sides:
-8x + 11 - 11 = 7 - 11
-8x = -4

Now.....take it from there.